(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the impact of internal organizational factors represented by dimensions of (organizational structure, organizational resources, organizational culture, strategic environment) on the performance of human resource management in its dimensions (efficiency and effectiveness). The study used descriptive analytical approach to achieve the objectives of the study and test its hypotheses, and the questionnaire was also developed for collecting the primary data from the study population, which reached (960) workers in 5 Yemeni private universities, where the random stratified sampling method was used to select the study sample which reached (274) elements. The data were statistically processed using the Statistical Package for Social Sciences (SPSS). The study findings revealed a statistically significant impact of all dimensions of internal organizational environment factors on the performance of human resources management, where the organizational structure dimension was the most impact, while the strategic environment dimension was the least impact on the performance of human resources management in Yemeni private universities. The findings also showed a high level of internal organizational environment factors available at Yemeni private universities. Based on the study findings, the study recommends Yemeni private universities to pay more attention to enhance the factors of the internal organizational environment, due to their impact on the performance of human resources management and improving the level of the general performance of the universities, as well as to focus on workers of those universities through taking care of their needs, training, motivation, and their functional development. The study also recommended that the study universities need to enhance and improve the level of culture of the importance of human resource management, with the aim of increasing performance efficiency and effectiveness, which in turn leads to achieving goals efficiently and effectively.